2002
DOI: 10.1159/000064284
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Hypercalciuria in Japanese Children

Abstract: Background/Aim: There are several factors, such as race, age, sex, and geographical variations, associated with renal stone formation. Although it is known that the prevalence of urolithiasis in Japanese children is low, the reason remains obscure. We hypothesize that the low prevalence of urolithiasis is associated with the urinary calcium excretion. The aim of our study was to investigate the prevalence of hypercalciuria in Japanese children. Methods: This investigation is a population-based school survey. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
3
21
1
3
Order By: Relevance
“…In Japan, the prevalence of hypercalciuria was only 0.6% in 529 school-age children, though the limit value for UCa/ Cr was considered 0.17 (18). It was thought that this low prevalence of hypercalciuria was related with low calcium and dietary salt intake, and this could be one of the causes of the low incidence of urolithiasis in Japan (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, the prevalence of hypercalciuria was only 0.6% in 529 school-age children, though the limit value for UCa/ Cr was considered 0.17 (18). It was thought that this low prevalence of hypercalciuria was related with low calcium and dietary salt intake, and this could be one of the causes of the low incidence of urolithiasis in Japan (18).…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that this low prevalence of hypercalciuria was related with low calcium and dietary salt intake, and this could be one of the causes of the low incidence of urolithiasis in Japan (18). In a study conducted with children aged between 5 and 12 years in India, the prevalence of hypercalciuria was 6.5% (19).…”
Section: Discussionmentioning
confidence: 99%
“…15 For example, in Eastern Europe countries, IH prevalence ranges between 3% and 7%; while in other countries it is as follows: Spain: 3.8%, Germany: 8.6%, Italy: 9.1%; United States of America: 10%, Japan: 0.6%, and Brazil: 3.2%. 6,9,15,18,[26][27][28][29] Moreover, such variability has been observed among different regions in the same country. For example, four Iranian studies reported that IH prevalence was 0.2%, 3.6%, 11.4%, and 13.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, it is possible to infer that IH rate among children 6 6 included in our study is higher than in the general population. 6,9,15,18,[26][27][28][29] Besides, IH prevalence in children with VUR had been previously studied because VUR prevalence among children with kidney stones (4%-8%) 31 is higher than in the healthy population (<1%) 32 . García Nieto described a very high rate (58.6%) of IH compared to the general population of his country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation